Childhood victimization and subsequent risk for promiscuity, prostitution, and teenage pregnancy: a prospective study - Widom, C S; Kuhns, J B (American journal of public health (1971), 1996)
OBJECTIVES: This study examined the extent to which being abused and/or neglected in childhood increases a person's risk for promiscuity, prostitution, and teenage pregnancy. METHODS: A prospective cohorts design was used to match, on the basis of age, race, sex, and social class, cases of abused and/or neglected children from 1967 to 1971 with nonabused and nonneglected children; subjects were followed into young adulthood. From 1989 to 1995 1196 subjects (676 abused and/or neglected and 520 control subjects were located and interviewed. RESULTS: Early childhood abuse and/or neglect was a significant predictor of prostitution for females (odds ratio [OR] = 2.96). For females, sexual abuse (OR = 2.54) and neglect (OR = 2.58) were associated with prostitution, whereas physical abuse was only marginally associated. Childhood abuse and neglect were not associated with increased risk for promiscuity or teenage pregnancy. CONCLUSIONS: These findings strongly support a relationship between childhood victimization and subsequent prostitution. The presumed causal sequence between childhood victimization and teenage pregnancy may need to be reevaluated.